2011
DOI: 10.1603/en11029
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Volatile Pheromone inAgrilus planipennisFairmaire (Coleoptera: Buprestidae) That Increases Attraction to a Host Foliar Volatile

Abstract: Analysis by gas chromatography/mass spectrometry (GC/MS) of volatiles from virgin female emerald ash borer, Agrilus planipennis Fairmaire confirmed the emission of (3Z)-lactone [(3Z)-dodecen-12-olide] but not its geometric isomer, (3E)-lactone [(3E)-dodecen-12-olide]. Gas chromatographic/electroantennographic (GC/EAD) analysis of synthetic (3Z)-lactone, which contained 10% (3E)-lactone, showed a strong response of male and female antennae to both isomers. EAG analysis with 0.01- to 100-μg dosages showed a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(125 citation statements)
references
References 40 publications
7
117
0
Order By: Relevance
“…In a series of sensory deprivation experiments, Pureswaran and Poland (2009) demonstrated that male EAB require their antennae to detect females, suggesting the existence of volatile chemical cues. Based on subsequent trapping experiments, we demonstrated that captures of males on green prism traps placed in the canopy and baited with both (3Z)-lactone and (3Z)-hexenol were up to 100 % higher compared with trap catches in traps baited with (3Z)-hexenol alone (Silk et al 2011). Higher captures occurred particularly when traps were placed in the ash canopy (Ryall et al 2012(Ryall et al , 2013.…”
Section: Introductionmentioning
confidence: 92%
“…In a series of sensory deprivation experiments, Pureswaran and Poland (2009) demonstrated that male EAB require their antennae to detect females, suggesting the existence of volatile chemical cues. Based on subsequent trapping experiments, we demonstrated that captures of males on green prism traps placed in the canopy and baited with both (3Z)-lactone and (3Z)-hexenol were up to 100 % higher compared with trap catches in traps baited with (3Z)-hexenol alone (Silk et al 2011). Higher captures occurred particularly when traps were placed in the ash canopy (Ryall et al 2012(Ryall et al , 2013.…”
Section: Introductionmentioning
confidence: 92%
“…Despite this, some Coleopteran families have received little attention, particularly Buprestidae. The exception is the great number of laboratory and field studies reported on the emerald ash borer (EAB), Agrilus planipennis (Fairnaire) (Coleoptera: Buprestidae), an invasive species originating from Asia that has caused considerable mortality of ash trees in the US and Canada (Bartelt et al, 2007;De Groot et al, 2008;Francese et al, 2008;Lelito et al, 2008;Lelito et al, 2009;Silk et al, 2009;Crook and Mastro, 2010;Silk et al, 2011), and some field experiments to catch different jewel beetles (Montgomery and Wargo, 1983;McIntosh et al, 2001). The black-banded oak borer (BBOB) Coroebus florentinus (Herbst) (Coleoptera: Buprestidae), together with its sister species C. undatus, produce notable damage to cork trees, thereby reducing the production of high quality cork.…”
Section: Introductionmentioning
confidence: 99%
“…However, other investigations resulted in the discovery of two hydrocarbons as female contact pheromones, which are probably involved in mate recognition (Lelito et al, 2009;Silk et al, 2009). Moreover, a recent study showed that a volatile pheromone produced by the EAB in combination with foliar volatiles was highly attractive to conspecific individuals (Silk et al, 2011). In the BBOB, male antennae are much longer and contain more olfactory sensilla basiconica than those of females (unpublished), which could suggest also a likely role for a sex pheromone in this species.…”
Section: Introductionmentioning
confidence: 99%
“…With the optimal foliar locations for positioning branch traps now being known, it will thus be useful to determine which odor blend might further optimize their effi cacy. In addition to the (Z)-3-hexen-1-ol lures used previously in 2013, (3Z)-dodecen-12-olide pheromone might further increase attraction, as shown for other trap designs (Silk et al, 2011).…”
Section: Discussionmentioning
confidence: 71%